1995
DOI: 10.1042/bj3110445
|View full text |Cite
|
Sign up to set email alerts
|

Co-localization and functional coupling of creatine kinase B and gastric H+/K+-ATPase on the apical membrane and the tubulovesicular system of parietal cells

Abstract: Immunogold labelling of creatine kinase B (BB-CK) and gastric H+/K(+)-ATPase in the parietal cells of the stomach revealed colocalization of these two enzymes on the apical membrane and the membranes of the tubulovesicular system. Upon fractionation of hog parietal cells, a specific fraction of the BB-CK proteins remained associated with the purified vesicles, in which gastric H+/K(+)-ATPase is highly enriched. The BB-CK present in this highly purified preparation was able to support pronounced H+/K(+)-ATPase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 34 publications
3
24
0
Order By: Relevance
“…CK activity has been shown to maintain high local ATP concentration to fuel this active ion transport. Predominant localization to either apical (Keller and Gordon, 1991 ;Sistermans et al, 1995) or basolateral (Friedman and Roberts, 1992) membrane has been observed in different epithelia.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…CK activity has been shown to maintain high local ATP concentration to fuel this active ion transport. Predominant localization to either apical (Keller and Gordon, 1991 ;Sistermans et al, 1995) or basolateral (Friedman and Roberts, 1992) membrane has been observed in different epithelia.…”
Section: Discussionmentioning
confidence: 95%
“…As a corollary of this model, the socalled cytosolic forms of creatine kinase (MM and BB) must be spatially localized. Abundant evidence indicates that both MM-CK and BB-CK can form specific, stable associations with both plasma and intracellular membranes (Clark et al, 1993 ;Keller and Gordon, 1991 ;Korge et al, 1993 ;Korge and Campbell, 1994 ;Lim et al, 1983 ;Perryman et al, 1985 ;Rossi et al, 1990 ;Sistermans et al, 1995 ;Wallimann and Hemmer, 1994).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Functional coupling between and creatine kinase is also reported in the parietal cells of the stomach (Sistermans et al, 1995). Thus, ATP regeneration by creatine kinase is necessary for many cell functions.…”
Section: Introductionmentioning
confidence: 94%